2015
DOI: 10.1080/15389588.2015.1043128
|View full text |Cite
|
Sign up to set email alerts
|

Effects of digital countdown timer on intersection safety and efficiency: A systematic review

Abstract: Due to the limited and inconsistent evidence regarding DCTs' effects on intersection safety and efficiency, it is not sufficient to recommend any type of DCT to be installed at signalized intersections to improve safety and operational efficiency. Nevertheless, it is apparent that both RSCTs and CCTs enhance intersection capacity, though their impacts on intersection safety are unclear. Future studies need to further verify those anticipated safe and operational benefits of DCTs with enriched field observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Thirty-five (35) of the systematic reviews in the overview included studies from high-income countries. Only one review [ 50 ] included studies from high-income, upper-middle and low-income countries. One systematic review did not find any studies that met the inclusion criteria despite the search being updated twice [ 41 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-five (35) of the systematic reviews in the overview included studies from high-income countries. Only one review [ 50 ] included studies from high-income, upper-middle and low-income countries. One systematic review did not find any studies that met the inclusion criteria despite the search being updated twice [ 41 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…The result from Opole city shows that would be better if drivers do not know the exactly time for ending the red signal. For Effects of countdown timers on traffic safety at signalized intersections example, countdown timer could only display counting of the rest of the signal without three last seconds (Fu, Zhang, Qi, & Cheng, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of countdown timers at signalized intersections changes the way traffic control signals are perceived by drivers (Felicio, Grepo, Reyes, & Yupingkun, 2015, Huang, Fujita, & Wisinee, 2017Rijavec, Zakovšek, & Maher, 2013). Depending on the nature of the driver this may be a source of stress or motivation to act too quickly when the lights change, and could be the reason for dangerous incidents such as entries onto the intersection at red signals or rear end collisions (Devalla, Biswas, & Ghosh, 2015;Napiah, Koh, & Che Long, 2007, Botzoris, Papakatsikas, Profillidis, & Galanis, 2017Fu, Zhang, Qi, & Cheng, 2016;Biswas, Ghosh, & Chandra, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Safety characteristics of SCTs were investigated in [54] for not only a GSCT and an RSCT but also CCT a (continuous countdown timer-displaying all signals) The literature was researched using the PRISMA method and 79 references were analyzed, of which 14 were thoroughly investigated. It was found that the effect of countdown timers is dependent on the type of device, and different parameters in different studies indicated improvement or lack thereof.…”
Section: Safety (Number Of Crashes Vehicle-vehicle Conflicts)mentioning
confidence: 99%